Development of Biology Interactive Learning Multimedia on Animal Tissue Topic in The Class XI IPA in SMA Yapis Manokwari - Bahtiar, Wisnu Aziz; Nunaki, Jan Hendrik; Iwan, I. Iwan (Inornatus: Biology Education Journal, 2018)
The development research aims to develop interactive multimedia-based learning media on valid, practical and effective animal tisue material. This development research refers to the ADDIE development model. Based on the data analysis obtained value of validity and media based on material expert got the value of o,92 with valid category while in terms of media diperolch value of validty for interactive learning media 0,94 with valid category, practice media obtained from the observation aheet of instructional media implementation with a value of 91,67 with good category meanwhile for the effectiveness aspect derived from 4 assessmet of student active with a value of 98,30 where the learning media is said to be effective in learning if the activities of learners in the lesson 75% the ability of teachers to manage learning with the acquisition value of 3,28 are included in the category of moderate, test results learners with completeness of individual acquisition of 21 people with mastery mask 95,5% and quistonnaire response of learners with the acquisition of 75,76 learners respond positively to interactive media learning